2013
DOI: 10.1002/cctc.201300181
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure of Bimetallic PtPd Catalysts under Oxidizing Conditions

Abstract: Diesel oxidation catalysts (DOCs), which decrease the amount of harmful carbon monoxide (CO), nitrogen oxide (NO), and hydrocarbon (HC) emissions in engine exhaust, typically utilize Pt and Pd in the active phase. There is universal agreement that the addition of Pd improves both the catalytic performance and the durability of Pt catalysts. However, the mechanisms by which Pd improves the performance of Pt are less clear. Because these catalysts operate under oxidizing conditions, it is important to understand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
88
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(101 citation statements)
references
References 27 publications
13
88
0
Order By: Relevance
“…The compositions of the Pt-Pd particles of these regions on the model catalysts are included in Fig. 6, and the observations are similar to those reported by us previously on a supported catalyst [12], where EXAFS, XRD, and STEM-EDS confirmed that the composition of the individual particles in the aged catalyst mirrors that of the initial catalyst. The results show clearly that Pt and Pd mobile species are emitted from these nanoparticles and the rates of their transport are similar, leading to similar compositions of the larger particles that are formed.…”
Section: Short-term (62 Min) Aging Studies In the Sabretube™ Furnacesupporting
confidence: 86%
See 2 more Smart Citations
“…The compositions of the Pt-Pd particles of these regions on the model catalysts are included in Fig. 6, and the observations are similar to those reported by us previously on a supported catalyst [12], where EXAFS, XRD, and STEM-EDS confirmed that the composition of the individual particles in the aged catalyst mirrors that of the initial catalyst. The results show clearly that Pt and Pd mobile species are emitted from these nanoparticles and the rates of their transport are similar, leading to similar compositions of the larger particles that are formed.…”
Section: Short-term (62 Min) Aging Studies In the Sabretube™ Furnacesupporting
confidence: 86%
“…Accelerated aging of Pt catalysts is generally carried out in air at atmospheric pressure where we see rapid sintering at elevated temperatures [12,13]. Furthermore, air aging leads to similar catalyst deactivation as that seen in vehicle aging [14].…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Doping and alloying can be used to tune the properties of bulk Pt. Alloying Pt with Sn 9 and Zn 10,11 has been used for selectivity control and with Pd to reduce sintering 12,13 . Here, our inspiration is drawn from the boration (boron--doping) of extended surfaces of Co and Ni, used in Fischer--Tropsch synthesis and steam me--thane reforming, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…A similar effect is observed if the Pt 7 /alumina is exposed to a saturation dose of D 2 then heated to 700 K (not shown), consistent with the ISS suggesting thermal restructuring causing a small reduc--tion in the number of exposed Pt sites. 7 /alumina samples that were first exposed to a particular manipulation and then probed by CO TPD (10 L 13 CO expo--sure at 150 K, heating at 3 K/sec to 700 K).…”
mentioning
confidence: 99%